Transcriptome analysis identified long non-coding RNAs involved in the adaption of yak to high-altitude environments - Jin-Wei Xin; Zhi-Xin Chai; Cheng-Fu Zhang; Yu-Mei Yang; Qiang Zhang; Yong Zhu; Han-Wen Cao; Cidan Yang Ji; Jin-Cheng Zhong; Qiu-Mei Ji (Royal Society Open Science, 2020)
The mechanisms underlying yak adaptation to high-altitude environments have been investigated using various methods, but no report has focused on long non-coding RNA (lncRNA). In the present study, lncRNAs were screened from the gluteus transcriptomes of yak and their transcriptional levels were compared with those in Sanjiang cattle, Holstein cattle and Tibetan cattle. The potential target genes of the differentially expressed lncRNAs between species/strains were predicted using cis and trans models. Based on cis-regulated target genes, no KEGG pathway was significantly enriched. Based on trans-regulated target genes, 11 KEGG pathways in relation to energy metabolism and three KEGG pathways associated with muscle contraction were significantly enriched. Compared with cattle strains, transcriptional levels of acyl-CoA dehydrogenase, acyl-CoA-binding protein, 3-hydroxyacyl-CoA dehydrogenase were relatively higher and those of glyceraldehyde 3-phosphate dehydrogenase, phosphoglycerate mutase 1, pyruvate kinase and lactate/malate dehydrogenase were relatively lower in yak, suggesting that yaks activated fatty acid oxidation but inhibited glucose oxidation and glycolysis. Besides, NADH dehydrogenase and ATP synthase showed lower transcriptional levels in yak than in cattle, which might protect muscle tissues from deterioration caused by reactive oxygen species (ROS). Compared with cattle strains, the higher transcriptional level of glyoxalase in yak might contribute to dicarbonyl stress resistance. Voltage-dependent calcium channel/calcium release channel showed a lower level in yak than in cattle strains, which could reduce the Ca2+ influx and subsequently decrease the risk of hypertension. However, levels of EF-hand and myosin were higher in yak than in cattle strains, which might enhance the negative effects of reduced Ca2+ on muscle contraction. Overall, the present study identified lncRNAs and proposed their potential regulatory functions in yak.